Estrututa genealogica e variabilidade genética de ovinos morada nova da variedade branca - Sales, Daniel Caetano (Universidade Federal Rural do Semi-Árido, 2021)
The Morada Nova sheep of the white variety are animals adapted to the atypical conditions of the Brazillian semiarid region with the capacity to be raised for consumption in a sustainable way. The purpose of this study was to evaluate the genetic variability and population structure of the white Morada sheep in four herds. The parameters on the population evaluated were the effective number of founders (fe) and ancestors (fa), effective population size (Ne), inbreeding coefficient (F), inbreeding increase (ΔF), and pedigree integrity, estimated using ENDOG 4.8 software. (GUTIERREZ AND GOYACHE, 2005), and a genealogy record of 219 animals, born between 2018 to 2021, was used. Of the total number of animals studied, 44.74% did not have pedigree information on their mother or father and 50.47% did not have available information on their grandparents, where 52.97% had a pedigree in their first ancestry (obtained through the average of known parents); 23.74% in the second; 13.58% in the third; and 5.33% in the fourth. The effective size was 10.7, considering the complete equivalent generation. The effective number of founding animals (fe) and ancestors (fa) was 10, which indicates the effective participation of all founding animals in the population over the generations. Therefore, reducing losses of genetic variability. Of all the ancestors, only 3 were responsible for explaining 50% of the population’s genetic variability, reflecting the low values of fa and fe. The population’s average inbreeding and kinship coefficients were 2.61 and 4.54. The F statistics of Wright, Fis, Fst, and Fit, were -0.012, 0.016, and 0.003. This indicates the absence of under-structure of the population.
Keywords: Ovinos; Endogamia; Parentesco; Pedigree; População; Sheep; Inbreeding; Kinship; Pedigree; Population; CIENCIAS AGRARIAS::ZOOTECNIA